Sustainable Ecotourism Potential of Central Kalimantan’s Peatlands: Strategies for Regional Economic Growth - Irawan; Wiwin Zakiah; Yudi Pungan; Fujun La (New Advances in Business, Management and Economics Vol. 3, 2025)
Ecotourism is “responsible travel to natural areas that conserves the environment, sustains the well-being of the local people, and involves interpretation and education. Peatlands are vital natural ecosystems that contribute significantly to biodiversity protection, climate management, and human well-being. Indonesia is the world’s fourth largest country, with peat deposits covering 20.6 million hectares primarily in Sumatra, Kalimantan, and Papua New Guinea. The purpose of this study is to identify and analyze the potential and strategy for developing peat areas as sustainable ecotourism objects. This research was conducted using a field explanation to see firsthand the potential of peat areas as ecotourism destinations. Primary data collection was carried out directly by means of interviews and questionnaires to 150 respondents by purposive sampling. Analysis of the data used the Guidelines for Assessment of Tourist Attractions Basin on the ADO-ADTWA Guidelines of the Directorate General of PHKA, 2003. The three categories of development potential include Category A-Potential to be Developed, Category B-Sufficient Potential to be Developed and Category C-Not Potential to be Developed. Meanwhile, the analysis of ecotourism development strategies for the peat area uses SWOT analysis and Process Hierarchy Analysis. The Results showed (1) Central Kalimantan peatland area quite the potential to be developed as an ecotourism destination, (2) The development strategy was chosen as a strategy of rapid growth and stable growth to improve the tourist visit to the peatlands, (3) The indicator of the attractiveness of the peatlands of Central Kalimantan as the first rank and the reason for tourists to visit ecotourism in the peatlands. The potential attraction of peatland ecotourism destination in Sebangau National Park peatlands, the Sungai Koran, Resort Mangkok and Punggualas destination, including category B, is quite potential to be developed as an ecotourism object in Central Kalimantan.